THE IMPLEMENTATION OF THE WRITING PROCESS IN TEACHING WRITING FOR YOUNG LEARNERS - Hertiki Hertiki (Journal of English for Academic and Specific Purposes (JEASP), 2018)
In writing class, young learners need the guidance from the teacher to express their ideas to do the writing task. This study is intended to observe how the teacher implemented the writing process in teaching writing. The implementation of the writing process includes three important things - the techniques, teaching aids, and the teaching procedures. This study was a case study. It was conducted in twelve meetings at Primary 3 Class where the researcher was the non-participant observer so she did not take any participation in the teaching-learning activities. The researcher obtained the data from classroom observations, pictures taking, field notes, and interviews. The results showed that the teacher implemented the writing process in teaching writing by using seven kinds of teaching techniques, eight kinds of teaching aids and different teaching procedures for each technique. The seven techniques were brainstorming, mind mapping, drawing, reading activities, browsing on the internet, pair or group work, and individual writing. The techniques were supported by eight kinds of teaching aids such as storybooks, journal books, whiteboard, workbooks, some stationary items, computers, a laptop, and a LCD projector. The reason for using the techniques, the teaching aids and the procedures were to guide and motivate the students to write better in class. In conclusion, the teaching techniques, teaching aids, and teaching procedures used by the teacher made the students become more active and the students were encouraged to express their ideas in the written work in class